The Influence of Online Self-Regulated Learning on BIPA Teaching Material Development Skills Using the Canva Application - Indriyani, Vivi; Fendi, Hasri; Haron, Rohaidah Binti (Universitas Muhammadiyah Malang, 2024)
Creating instructional materials is an essential responsibility for educators during the process of teaching and learning. Prospective instructors can learn skills in compiling instructional materials during their undergraduate studies. This technique entails the utilization of students' writing proficiency and autonomous capabilities in developing inventive instructional resources. The CANVA program is a useful tool for creating educational materials. Presently, higher education can be pursued through both traditional in-person instruction and online platforms. This project employs the Online Self-Regulated Learning (SRL) technique and utilizes e-learning tools to generate Indonesian language teaching materials for Foreign Speakers (BIPA). The research is to examine the influence of Online Self-Regulated Learning on the proficiency in creating BIPA teaching materials using the Canva application among aspiring Indonesian language instructors at Padang State University. This research employed experimental methodologies and quasi-experimental designs, specifically utilizing a posttest only control design. The group under study comprises students enrolled in the 2020 cohort of the PBSI Study Program. Purposive sampling strategies were employed to choose two classes as samples for this investigation. The research instrument is an assessment tool. The data analysis process included conducting normality and homogeneity tests on the data, followed by performing the Independent Sample T Test. The results indicated that the data did not follow a normal distribution, thus it was analyzed using Mann U Whitney non-parametric statistics. The test results indicate a notable disparity in the mean learning outcomes between students who employ the Online Self-Regulated Learning technique to create BIPA teaching materials using the Canva application, and students who utilize the assignment method.